Langerhans' cell histiocytosis with neurological injuries diagnosed from a single cutaneous lesion - Bannach, Andréa Bauer (An Bras Dermatol, 2017)
Histiocytoses are rare diseases caused by the proliferation of histiocytes. The pathogenesis remains unknown and the highest incidence occurs in pediatric patients. The clinical presentations can be varied, in multiple organs and systems, and the skin lesions are not always present. Evolution is unpredictable and treatment depends on the extent and severity of the disease. It is described the case of a patient with various neurological symptoms, extensively investigated, who had its was diagnosed with histiocytosis from a single skin lesion. This report highlights the importance of Dermatology in assisting the investigation of difficult cases in medical practice.